Initial experience with endoscopic sleeve gastroplasty: technical success and reproducibility in the bariatric population - Sharaiha, Reem Z.; Kedia, Prashant; Kumta, Nikhil; DeFilippis, Ersilia M.; Gaidhane, Monica; Shukla, Alpana; Aronne, Louis J.; Kahaleh, Michel (Endoscopy, 2015)
Background and aims: Novel endoscopic techniques have been developed as effective treatments for obesity. Recently, reduction of gastric volume via endoscopic placement of full-thickness sutures, termed endoscopic sleeve gastroplasty (ESG), has been described. Our aim was to evaluate the safety, technical feasibility, and clinical outcomes for ESG. Patient and methods: Between August 2013 and May 2014, ESG was performed on 10 patients using an endoscopic suturing device. Their weight loss, waist circumference, and clinical outcomes were assessed. Results: Mean patient age was 43.7 years and mean body mass index (BMI) was 45.2 kg/m2. There were no significant adverse events noted. After 1 month, 3 months, and 6 months, excess weight loss of 18 %, 26 %, and 30 %, and mean weight loss of 11.5 kg, 19.4 kg, and 33.0 kg, respectively, were observed. The differences observed in mean BMI and waist circumference were 4.9 kg/m2 (P = 0.0004) and 21.7 cm (P = 0.003), respectively. Conclusions: ESG is effective in achieving weight loss with minimal adverse events. This approach may provide a cost-effective outpatient procedure to add to the steadily growing armamentarium available for treatment of this significant epidemic.